SOCIAL CLASS AND INEQUALITY IN A DYSTOPIAN FUTURE: A STUDY OF KLARA AND THE SUN BY KAZUO ISHIGURO - Deka, Kishor Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Kazuo Ishiguro’s Klara and the Sun (2021) presents a dystopian future where social class and inequality are amplified by technological advancements, particularly in the realm of artificial intelligence. The novel’s protagonist, Klara, an Artificial Friend (AF), provides a unique lens through which we can examine the intersection of technology and socio-economic stratification. Through Klara’s observations of human interactions, we are introduced to a world where access to resources such as education, health, and even the potential for human "elevation" are determined by one’s social class. This paper explores how Ishiguro critiques class inequality and social division through the experiences of Klara and the characters surrounding her. It argues that Klara and the Sun highlights the consequences of a hyper-competitive, technology-driven society, wherein social mobility is limited, and the gap between the privileged and the marginalized is only exacerbated by technological innovations. Drawing on socio-economic theory and literary analysis, the paper examines how the novel critiques the dystopian world’s stratified social structure, using AI and biotechnology as metaphors for the dangers of an unequal society.